Ultrafast laser manufacturing: from physics to industrial applications. Issue 2 (2021) - Orazi, L.; Romoli, L.; Schmidt, M.; Li, L.
Abstract: Modern ultrafast lasers are enabling better operative performances in micro and nano-fabrications of materials, benefited from their ease of use, robustness, and reliability. The purpose of this paper is to bridge the gap between the knowledge of ultrafast optics and the modern industrial applications. The paper introduces main phenomena in ultrafast laser-matter interactions by reviewing relevant theoretical models and simulation techniques. The operation of ultrafast lasers is based on nonlinear optics phenomena, fully described only in the framework of quantum-mechanics. Current trends in the development of modern ultrafast system are given. It also presents a review of the latest advances in ultrafast laser-based manufacturing processes, some of the most interesting industrial applications, and a discussion on future trends and challenges.